The news business - Chancellor, John (New American library, 1983)
In this unique blend of shop talk, exposition, anecdote and concrete example, two practicing newsmen take us inside the news business to show us how it works - on the air and in print. Each is an acknowledged master in his field, and their book has the easy authority, the authenticity and liveliness that proceed from hands-on experience and undimmed enthusiasm. In these pages, John Chancellor, commentator for NBC's "Nightly News," and Pulitzer Prize winner Walter R. Mears, vice-president and Washington bureau chief of the Associated Press, share their profound knowledge of their calling. Beyond this, they have produced a book that is itself a sterling instance of practicing what is preached. In organization, pacing and felicity of style, "The News Business" mirrors the structure and method of a successful news story. Its chapters move from the initial decision making (what events will be covered and which emphasized) through the all-important first sentence, or lead, to the body of the story and its essentials: deft use of illuminating detail, adroit analysis, precise wording, scrupulous treatment of sources and on to getting the story delivered. The last chapter offers the aspiring journalist hard-nosed but optimistic advice on starting out. Filled with inner-circle lore, great humor and irresistible zest, "The News Business" has the interest and charm of a skilled conversationalist at ease in a subject he knows and loves.